Digital Technologies for Innovation in Education: A Theorical Review of Learning Processes Mediated by Mobile Devices (2019)
Mobile devices stand in a prominent place on people's daily lives and the possibilities of learning through the mediation of these devices have become more relevant in recent years and have generated a significant contribution to education among learning subjects in higher education, worldwide. The objective of this review article is to present the most relevant research results that have been forged about mobile learning, bonding experiences in different parts of the world, most notable challenges and some guidelines for forthcoming research efforts. The results reveal that intentions in both, learning and teaching subjects, are influenced by various factors including relative advantage, complexity, social influence, perceived enjoyment, and self-management of learning processes. By picturing students' willingness to embrace mobile learning, this study offers useful and helpful implications for application and content developers who can guide the design and implementation of comprehensive learning systems.